2013
DOI: 10.4067/s0718-221x2013005000012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal pre-treatment and variables of production on properties of OSB panels of Pinus taeda

Abstract: The main objective of this study was to compare the effect of thermal pre-treatment in particles of strand type with the effect of variables of production on physical-mechanical properties of OSB panels, aiming to improve their dimensional stability. The experimental design consisted on five treatments with the assessment of two temperatures of thermal treatment on particles (200 and 240°C) during 60 minutes; the increase of adhesive content, the application of paraffin in different treatments and a control tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
5
0
4
Order By: Relevance
“…De acordo com Carvalho et al (2015) o tratamento térmico também pode ser uma alternativa no aprimoramento da estabilidade dimensional dos painéis produzidos, por reduzir a afinidade com água, uma vez que, visa degradar a hemicelulose e liberar a tensão de compressão formada durante a prensagem, porém o calor durante o processo pode promover a redução das propriedades mecânicas (Mendes et al, 2013).…”
Section: A B Cunclassified
See 1 more Smart Citation
“…De acordo com Carvalho et al (2015) o tratamento térmico também pode ser uma alternativa no aprimoramento da estabilidade dimensional dos painéis produzidos, por reduzir a afinidade com água, uma vez que, visa degradar a hemicelulose e liberar a tensão de compressão formada durante a prensagem, porém o calor durante o processo pode promover a redução das propriedades mecânicas (Mendes et al, 2013).…”
Section: A B Cunclassified
“…Essa condição promove a maior penetração das moléculas de água nos espaços submicroscópicos localizados entre as microfibrilas, provocando a expansão destas devido ao afastamento das mesmas. Segundo Mendes et al (2013) esse acúmulo das moléculas de água nas cavidades celulares gera maiores agravos as propriedades físicas dos painéis aglomerados.…”
Section: A B Cunclassified
“…All treatments in this study met this requirement for OSB panels used for structural purposes in humid environments. Mendes et al (2013b) studied Pinus taeda and verified that the moisture content decreased from 8.55 to 7.64% when using a heat treatment of 200°C (473 K) on the strands. When the panels went through a heat treatment without the replacement of atmosphere, their values were higher than the values found in this study.…”
Section: Resultsmentioning
confidence: 86%
“…Poubel, Garcia, Santos, Oliveira, and Abreu (2013) performed a thermal treatment on Pinus caribaea wood and observed a decrease in the density at 200°C (473 K). Mendes et al (2013b) showed a decrease in the density in relation to a controlled temperature of 240°C (513 K), where a thermal treatment was made on strands with atmosphere replacement. Values varied from 694 to 746 kg*m -3 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in wet conditions, the IB values were 0.16 N/mm 2 and 0.24 N/mm 2 for the commercial and red maple OSBs, respectively, for boards with thicknesses of 0.025 inches, 0.035 inches, and 0.045 inches. The IB ranged from 0.39 N/mm 2 to 0.43 N/mm 2 and decreased to the range of 0.13 N/mm 2 to 0.18 N/mm 2 after the boil test for boards with 10 mm thick (Ciobanu et al 2014 (Mendes et al 2013). Also, the values of the IB, MOR (parallel), and MOE (parallel) were 0.495 MPa to 0.950 MPa, 69 MPa to 72 MPa, and 8135 MPa to 9050 MPa, respectively, for aspen/birch OSB-Ponderosa pine OSB bonded with PVA type I with thickness of 12 mm (Barbuta et al 2012).…”
mentioning
confidence: 93%